2021
DOI: 10.11628/ksppe.2021.24.4.429
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and psychological effects of forest healing focused on plant fragrance therapy for maladjusted soldiers

Abstract: Background and objective: This study verified the physiological and psychological effects of plant fragrance therapy to analyze whether the therapy has a forest healing effect on maladjusted soldiers. Methods: This study was conducted from March 14 to May 31, 2020 according to the Green Camp curriculum for 2 weeks per recruit class. Thus, plant fragrance therapy was implemented twice each for three recruit classes. Each session of the program was carried out for 4 hours from 1 p.m. to 5 p.m. The venue was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Several studies have investigated the effectiveness of an ASFHP as a nonpharmacological treatment for cognitive decline and reported positive effects on mood, immune system, stress levels, and physical health. 7 10 11 19 In a meta-analysis, forest-based intervention showed a significant effect on overall mental health. 20 In a previous study, similar ASFHP conducted on MCI patients showed positive effects on psychological, physiological, and physical health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the effectiveness of an ASFHP as a nonpharmacological treatment for cognitive decline and reported positive effects on mood, immune system, stress levels, and physical health. 7 10 11 19 In a meta-analysis, forest-based intervention showed a significant effect on overall mental health. 20 In a previous study, similar ASFHP conducted on MCI patients showed positive effects on psychological, physiological, and physical health.…”
Section: Discussionmentioning
confidence: 99%
“…9 The FOWI provides forest therapy through a forest healing program and has continuously tried to prove the program’s effectiveness in the management of cognitive and psychological disorders. 10 11 …”
Section: Introductionmentioning
confidence: 99%
“…Only recently, a few studies investigated the most important psychophysiological short-term effects of individual exposure to plantemitted MTs. However, such studies were limited to specific and/or numerically scarce target groups, for example, maladjusted soldiers [45], or to specific plant species, such as Cinnamomum burmannii, growing in partially controlled environments [46]. In general, even though the results of these studies are encouraging, quantitative experiments in natural environments are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the evidence about MTs activity on human health mostly derives from in vitro or animal or indoor/laboratory experiments, usually with a small number of study participants [43], and very few studies taking into consideration MTs concentration along with the measurement of health outcomes [23,44]. Only recently, a few studies investigated the most important psychophysiological short-term effects of individual exposure to plant-emitted MTs, but such studies were limited to specific and/or numerically scarce target groups, for example, maladjusted soldiers [45], or to specific plant species, for example Cinnamomum burmannii, growing in partially controlled environments [46]. In general, even though the results of these studies are encouraging, quantitative experiments in natural environments are still lacking.…”
Section: Introductionmentioning
confidence: 99%